DEVELOPING A GROWTH MINDSET IN ELEMENTARY SCHOOL TEACHERS: A TRAINING GUIDE TO ENHANCE DEEP LEARNING - Wahdeni; Tuti khairani; Khairani Hasibuan; Hamka (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The training program “Developing a Growth Mindset Among Elementary School Teachers: A Training Guide for Enhancing Deep Learning” was organized by the Department of Education of Mandailing Natal Regency to strengthen teachers’ pedagogical competence and foster a student-centered learning culture. This initiative was motivated by the 2022 PISA results, which revealed that more than 99% of Indonesian students could only solve problems at lower levels (Lower Order Thinking Skills), while less than 1% reached higher levels (Higher Order Thinking Skills). One of the underlying causes is the prevalence of a fixed mindset among teachers—the belief that intelligence is innate and difficult to change. This training aimed to cultivate a growth mindset based on Carol S. Dweck’s (2006) theory, which emphasizes that abilities can be developed through effort and learning strategies. The method employed was a reflective andragogical workshop involving material presentations, microteaching simulations, and collaborative reflections. The results indicated a significant improvement in teachers’ understanding of the growth mindset concept and its implementation in deep learning. Teachers began providing process praise, applying The Power of Yet strategy, and creating emotionally safe and collaborative classroom environments. Furthermore, the establishment of the Growth-Oriented Teacher Community of Mandailing Natal (KGB-Madina) emerged as a sustainable platform for sharing best teaching practices and fostering continuous professional growth.